Pestalotiopsis anacardiacearum sp. nov. (Amphisphaeriaceae) has an intricate relationship with Penicillaria jocosatrix the mango tip borer - Maharachchikumbura, Sajeewa S. N.; Zhang, Yanmin; Wang, Yong; Hyde, Kevin D. (Phytotaxa, 2013)
Pestalotiopsis anacardiacearum sp. nov. is described from leaves of Mangifera indica from Yunnan Province, China. The taxon can clearly be distinguished from all known species of Pestalotiopsis by its morphology. Phylogenetic analysis based on combined multi-locus alignment of the internal transcribed spacer (ITS), partial β-tubulin and partial translation elongation factor 1-alpha (tef1) also distinguishes this taxon. It can be distinguished from previously recorded Pestalotiopsis pathogens on mango by having larger conidia. The species occurs on leaves of mango following death associated with the mango tip borer (Penicillaria jocosatrix).